Initial Assessment of the Marinduque State University on the Implementation of an Educational Organization Management System (EOMS) Certifiable to ISO 21001:2018 - Magcamit, Raoul (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the readiness of Marinduque State University (MarSU) to implement an Educational Organization Management System (EOMS) certifiable to ISO 21001:2018. Anchored on Total Quality Management, Organizational Communication Theory, the Plan-Do-Check-Act Cycle, and Stakeholder Theory, the study employed a descriptive-evaluative research design to examine the University's conformity with the requirements of the standard. Data were collected from key institutional stakeholders through purposive sampling using a researcher-developed ISO 21001:2018 assessment checklist and gap analysis matrix, complemented by document analysis and semi-structured key informant interviews. Gap analysis was used to determine the University's level of conformity, identify implementation gaps, and establish priority areas for improvement. The findings showed that MarSU substantially conforms to most ISO 21001:2018 requirements, demonstrating strengths in organizational context, leadership, planning, selected support and operational processes, performance evaluation, and continual improvement. Overall, the University achieved conformity in 19 of the 28 clauses and sub-clauses assessed, placing it within the certifiable category while identifying nonconformities related to the Quality Policy, Quality Management Representative, resource provision, infrastructure, competence management, stakeholder property, and stakeholder satisfaction monitoring. The study concludes that MarSU possesses a functional Educational Organization Management System and is well-positioned for ISO 21001:2018 certification, provided that the identified gaps are addressed through strengthened institutional procedures, documentation, and continuous monitoring. It recommends institutionalizing proactive quality management practices to achieve sustained compliance and continual improvement. This study supports Sustainable Development Goal 4 (Quality Education) by promoting learner-centered quality assurance and continuous educational improvement, and Sustainable Development Goal 16 (Peace, Justice and Strong Institutions) by strengthening institutional governance, transparency, and accountability. Its sustainability impact lies in providing evidence-based guidance for institutional quality enhancement, strategic planning, and the long-term implementation of an internationally recognized educational management system.
Keywords: Educational Organization Management System (EOMS); Gap Analysis; ISO 21001:2018; Marinduque State University; Quality Assurance; Readiness Assessment; State Universities and Colleges